MANAGING INFLATION: THE INDIAN SCENARIO - Tiwana, Ratneev (2008)
Inflation is generally defined as a continuous or persistent increase in the general price level or, alternatively, as a continuous or sustained reduction in the value of money. The rise in price level has an effect on the wages, real income, production, employment levels, etc. Inflation also negatively affects the rate of growth and also leads to reduction in savings and investments. Because of the harmful effects of inflation on the economy, it has become a major economic issue. Controlling inflation has been one of the main objectives of the central banks all over the world, and has now emerged as a major issue of immediate importance in India. Short term interest rate is the main instrument applied by most of the countries. In case there is constant increase in inflation rate, rate of interest is increased to curb inflation. But there is no clear empirical evidence concerning the influence of interest rates on inflation and there is very little evidence regarding the Indian scenario. Now, the main question is: Is this tool helpful for containing inflation and can it be successfully implied in India? In order to examine the effect of interest rates on inflation in India, a newly published concept of evaluation of causal relationships has been implemented in this dissertation. The findings show that interest rates have a negative effect on inflation, however, this result qualifies by the following means. Firstly, the interest rate affects inflation by a causal chain which includes money stock and though the net consequence as suggested by theory, the individual links in the chain are not. Secondly, the causal connection allows interest rates to be used only partially for controlling inflation.